2007
DOI: 10.1051/vetres:2007033
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial lipopolysaccharide stimulates bovine neutrophil production of TNF-α, IL-1β, IL-12 and IFN-γ

Abstract: -After intramammary infection, polymorphonuclear neutrophil leukocytes (PMN) are the first cells recruited into the mammary gland. Rapid recruitment of and bacterial phagocytosis and killing by PMN are the most effective defenses against establishment of bacterial infection. In addition to their phagocytic and bactericidal properties, PMN may play a key supportive role through secretion of cytokines during the innate immune response. We sought to determine whether bovine PMN produce cytokines in response to st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 45 publications
4
40
0
Order By: Relevance
“…[25][26][27] In Muc2 À/À mice, transcription of Timp3, Tnf shedding enzyme inhibitor, was significantly decreased, which implies that the Tnf shedding might be increased in Muc2 À/À mice. Transcription of Tnf receptor Tnfsf1b was also upregulated in Muc2 À/À mice, and high levels of Tnfsf1b can mediate inflammation in a ligand-independent fashion.…”
Section: Discussionmentioning
confidence: 97%
“…[25][26][27] In Muc2 À/À mice, transcription of Timp3, Tnf shedding enzyme inhibitor, was significantly decreased, which implies that the Tnf shedding might be increased in Muc2 À/À mice. Transcription of Tnf receptor Tnfsf1b was also upregulated in Muc2 À/À mice, and high levels of Tnfsf1b can mediate inflammation in a ligand-independent fashion.…”
Section: Discussionmentioning
confidence: 97%
“…1). Interferon-g (IFN-g), a pluripotent cytokine with a wide array of biological activities ranging from the modulation of immune responses to the regulation of cell proliferation and apoptosis (Andrianifahanana et al, 2007) was selected as a model drug because it is commonly detected by ELISA (Sohn et al, 2007). For comparison, protein A was also immobilized through conventional GA chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…They may play an important role in enhancing the biological response of bovine neutrophils to bacterial infections (Leite et al, 2002;Sohn et al, 2007). Rodriguez et al (2015) conducted immunohisto chemical study for cytokine expression in spontaneously infected animals and found out that M. bovis-associated pneumonic lesions consistently resulted in upregulation of TNF-α, IL-4, IL-10 and IFN-γ expression, but expression of IL-1α, IL-1β, IL-2, IL-6 and IL-8 did not exhibit significant differences between infected and normal lung from control calves.…”
Section: Resultsmentioning
confidence: 99%